The Effect of Islamic Financial Report Transparency on Customer Trust - Levi Yani; Lili Artati; Novi Astria Ningsih; Siti Mahmudah; Joni Hendra (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to examine and analyze whether the transparency of Islamic financial reports influences the level of customer trust, and to determine how large that influence is within Islamic financial institutions. This study employs a quantitative approach by distributing questionnaires to 30 respondents. The collected data were subsequently tested using the classical assumption test and simple linear regression. The results indicate that the data are normally distributed and satisfy the testing requirements. Based on hypothesis testing (t-test and F-test), a significance value of 0.000 was found, meaning that the transparency of Islamic financial reports has a very positive and significant effect on customer trust. Furthermore, the coefficient of determination test (R Square) yielded a value of 0.80, indicating that transparency of financial reports contributes 80% toward the formation of customer trust, while the remaining 20% is influenced by other factors outside the scope of this study. These findings are consistent with previous research affirming that information transparency is the primary key to preventing suspicion and building customer loyalty within the Islamic banking system.